Teacher Professional Development in Indonesia’s Remote Areas with Driven Educational Philanthropic Institutions - Sutomo, Moh.; Siregar, Epi Supriyani (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
The three main problems of education in Indonesia’s remote areas: policy, human resources, and funding, are still deeply rooted today. The government’s unequal attention to remote schools makes the quality of education worse. To overcome this and as an effort to support government programs, the Tanoto Foundation has been driven by funding remote schools and training for teachers to develop their professionalism. This study aims to analyze how the Tanoto Foundation supports the professional development of teachers in remote areas and how the facilitation program activities are carried out. This research uses a qualitative case study approach by extracting data using philanthropic program documents and interviews with teachers and facilitators in three provinces. The results that the driven by Tanoto Foundation are focused on funding support in the provision of facilities and infrastructure, as well as the ‘Service-Learning’ training facilitation program for teachers. Forms of facilitation activities such as Pelita Guru Mandiri and the PINTAR program have trained many teachers and produced various innovative and fun learning methods, as well as learning products that were exhibited at the Education Expo. The results contribute philanthropic institutions are driven not only by funding but also by the development of teacher professionalism, which is still low and does not receive attention.